The experiences of health care professionals, patients, and families of the process of referral and admission to intensive care: A systematic literature review. (February 2020) - Rees, Sophie; Griffiths, Frances; Bassford, Christopher; Brooke, Mike; Fritz, Zoe; Huang, Huayi; Rees, Karen; Turner, Jake; Slowther, Anne-Marie
Treatment in an intensive care unit can be life-saving but it can be distressing and not every patient can benefit. Decisions to admit a patient to an intensive care unit are complex. We wished to explore how the decision to refer or admit is experienced by those involved, and undertook a systematic review of the literature to answer the research question: What are the experiences of health care professionals, patients, and families, of the process of referral and admission to an intensive care unit? Twelve relevant studies were identified, and a thematic analysis was conducted. Most studies involved health care professionals, with only two considering patients' or families' experiences. Four themes were identified which influenced experiences of intensive care unit referral and review: the professional environment; communication; the allocation of limited resources; and acknowledging uncertainty. Patients' and families' experiences have been under-researched in this area.